Combining ability and heterosis for some quantitative traits in experimental maize hybrids - Azad, Mohammad Abul Kalam; Biswas, Bhabendra Kumar; Alam, Nazmul; Alam, Sheikh Shamimul (Plant Breeding and Seed Science, 2014)
In rabi season 2012, six diversed maize inbred lines were crossed in all possible combinations without reciprocals by using a half diallel mating design to obtain 15 single cross. Inbred parents and their F1 single crosses with a check were evaluated in rabi season 2013 to evaluate the role of general and specific combin-ing ability and heterosis for some quantitative traits. Significant general combining ability variances was observed only for cob height and specific combining ability variances were observed for plant height, cob height, cob length, cob girth, number of kernels per cob, cob weight and hundred grain weight. The GCA/SCA ratio was less than unity for all studied traits except shelling percentage; this means that these traits are pre-dominantly controlled by non-additive gene action. Based on GCA estimates, it could be concluded that the best combiners were ML01, ML05 and ML29 inbred lines for most of the studied traits. This result indi-cated that these inbred lines could be considered as good combiners for improving these traits. Significant positive SCA effects were found for all studied traits except number of kernels per row and shelling percent-age. Based on SCA effects, it could be concluded that the crosses ML01×ML02, ML02×ML05, ML02×ML29 and ML05×ML15 could be exploited by the maize breeders to increase maize yield. Three F1 hybrids such as ML02×ML15, ML02×ML29 and ML05×ML15 proved to be the outstanding hybrids to immediate further steps for commercial cultivation. In a conclusive decision the F1 hybrid, ML02×ML29 was the best combina-tion as evaluated through combining ability and standard heterosis.